Facilitators and Barriers in HIV Linkage to Care Interventions: A Qualitative Evidence Review - Tso, Lai Sze (AIDS, 2016)
OBJECTIVE: To synthesize qualitative evidence on linkage to care interventions for people living with HIV. DESIGN: Systematic literature review. METHODS: We searched nineteen databases for studies reporting qualitative evidence on linkage interventions. Data extraction and thematic analysis were used to synthesize findings. Quality was assessed using the CASP tool and certainty of evidence was evaluated using the CERQual approach. RESULTS: Twenty-five studies from eleven countries focused on adults (24 studies), adolescents (8 studies), and pregnant women (4 studies). Facilitators included community-level factors (i.e. task-shifting, mobile outreach, integrated HIV and primary services, supportive cessation programs for substance users, active referrals, and dedicated case management teams) and individual-level factors (encouragement of peers/family and positive interactions with healthcare providers in transitioning into care). One key barrier for people living with HIV was perceived inability of providers to ensure confidentiality as part of linkage to care interventions. Providers reported difficulties navigating procedures across disparate facilities and having limited resources for linkage to care interventions. CONCLUSIONS: Our findings extend the literature by highlighting the importance of task-shifting, mobile outreach, and integrated HIV and primary services. Both community and individual level factors may increase the feasibility and acceptability of HIV linkage to care interventions. These findings may inform policies to increase the reach of HIV services available in communities .